The costs of falls in the community to the North East Ambulance Service. Issue 6 (19th May 2006) - Newton, J L; Kyle, P; Liversidge, P; Robinson, G; Wilton, K; Reeve, P
Abstract : Background: This study set out to quantify the immediate costs to the North East Ambulance Service (NEAS) of attending to fallers. Methods: Data from the Newcastle, UK area were collated by NEAS to identify those aged over 65 who had fallen and required an assistance only call or were subsequently transported to an Accident and Emergency (A&E) department. The 2001 census data for the total population served by NEAS in Newcastle were obtained. Results: The total population of Newcastle over the age of 65 was 41 338. Over 7 months NEAS attended to 1504 falls in Newcastle (at £115 per call out, this equates to £172 960). The faller was transported to A&E on 1339 occasions, while 165 falls required assistance only (11% of total) (36 falls requiring NEAS assistance per 1000 Newcastle population aged over 65 in 7 months). The total time on site for ambulance crews attending to fallers was 377.1 h (15.7 days in 7 months or 2.25 days per month). As the cost of emergency ambulance time is £123/h, the total cost was £46 383.30. Therefore, in Newcastle, attending to fallers in the community costs NEAS £376 018 per year (£145.83 per fall or £9.10 per person over the age of 65 per year). Conclusion: NEAS attend to a significant number of older people who fall in the community. In Newcastle alone the cost of this service equates to over 2 days of emergency ambulance crew time per month. Studies are needed to determine whether responding to falls in the community differently would be cost effective.